The Potential of Mangrove Ecosystems as A Sustainable Ecotourism Product in The Mangrove Area of Kss Beach, Tangerang District - Magharetta Putriyani Halim; Budi Setiawan (Jurnal Syntax Transformation, 2023)
Mangrove forests have ecological, economic, research, educational and ecotourism functions. The decline in mangrove forest land has resulted in an increase in carbon in Indonesia and the loss of habitat for various types of marine biota and natural resources. Therefore, mangrove ecotourism is one way that can have a positive impact on protecting and preserving the environment and can improve the economy of the surrounding community. One of the potentials for mangrove ecotourism that can be developed is located at KSS Beach, Tangerang Regency. This research uses qualitative research by conducting observations, interviews and distributing questionnaires to the public and visitors at KSS beach. KSS Beach fulfills four elements in ecotourism, namely the element of education, the element of understanding, the element of conservation of natural resources and the element of increasing local community income, namely having mangrove forest exploration activities, mangrove education and mangrove planting. KSS Beach has three types of mangroves, namely Avicenniaceae, Rhizophoraceae, and Sonneratiaceae which can be a processed mangrove product that has sales value among the community. Therefore, KSS Beach requires further development and assistance from the government so that it can become a mangrove ecotourism that is widely known by the community.